2012
DOI: 10.1080/10410236.2011.619252
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Message Framing Within the Stages of Change on Smoking Cessation Intentions and Behaviors

Abstract: This study examines two commonly used and accepted theoretical models in health communication-the stages of change and message framing-to determine whether gain- or loss-framed messages are more effective at getting people to intend to quit smoking depending on their current stage of change (precontemplation, contemplation, or preparation). One hundred forty-eight current smokers were exposed to one of four gain- or loss-framed messages that emphasized the benefits of cessation or the costs of smoking. Message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…To check the message-framing manipulation, we included a single item after participants viewed the cigarette packs that read ‘The information on the packs focused on the benefits of quitting smoking’ with a 5-point Likert-type response ranging from 1 (‘Strongly disagree’) to 5 (‘Strongly agree’) 20. Plain packaging has been shown to increase occasional smokers’ attention to pictorial cigarette warnings using methods such as eye tracking 21.…”
Section: Methodsmentioning
confidence: 99%
“…To check the message-framing manipulation, we included a single item after participants viewed the cigarette packs that read ‘The information on the packs focused on the benefits of quitting smoking’ with a 5-point Likert-type response ranging from 1 (‘Strongly disagree’) to 5 (‘Strongly agree’) 20. Plain packaging has been shown to increase occasional smokers’ attention to pictorial cigarette warnings using methods such as eye tracking 21.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Message believability is also associated with knowledge, attitudes and beliefs, 14 and is an important mediator between message exposure and subsequent smoking-related behaviors. 12,13 One study assessing the effects of message believability showed that message believability was associated with intention to engage in smoking cessation behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Informed by the Extended Parallel Process Model (EPPM), 15 a recent meta-analysis showed the impact of lossframed appeals is increased when such messages also include content to promote efficacy beliefs that behavior change leads to positive outcomes or engender self-efficacy for behavior change. 16 Another meta-analysis of cigarette warning label research drew similar conclusions, showing that loss-framed appeals are impactful among smokers with high efficacy beliefs (e.g., self-efficacy to quit) and gain-framed messages are most impactful among smokers with high perceived risks.…”
Section: Introductionmentioning
confidence: 99%